Exploring the fluency and comprehensibility of a role-play-based speaking in a tourism are university - Yosabat Tinggi Tandipayuk; Fatimah Hidayahni Amin; Ghada Tosson Abd Al-Lateef; K. J. Vargheese (Center for Humanities and Innovation Studies, 2023)
This research aims to measure the performance of role-play-based speaking in a tourism area university. This research is projected to determine the student's fluency and comprehension level on role-play-based speaking in a tourism area university. This research also explores the implementation of role-play-based speaking in a tourism area university. The researchers employed exploratory research of the small sample size; twenty-nine students were selected purposively to participate in this study voluntarily. In this research, the instruments that researchers used were speaking tests and an interview guide. The speaking test is designed to measure English speaking proficiency. The speaking test focuses on students' fluency and comprehensibility levels through role-play-based speaking. The researchers used dialogue to measure the student's views on implementing role-play-based speaking; this data was obtained from the interview. The interview results were analyzed in three steps: data condensation, data display, drawing and verifying conclusion. This research demonstrates the students' level of role-play-based speaking. The result showed that role play can improve students speaking performance in fluency and comprehensibility. This research highlights the positive impact of role-play-based speaking activities in an English Tourism class. The findings suggest that students engaging in role-play exercises demonstrate good fluency and comprehensibility in spoken English. Moreover, lecturers and students benefit from this approach by gaining confidence and enjoyment in speaking. Through this exploratory research, researchers generated preliminary hypotheses, which can be further tested using other research designs like descriptive or experimental research.